TANGGUNG JAWAB GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER SISWA - Melati Y.F. Pasaribu; Priscila E. Girsang; Lasma Hutagalung; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
Christian Religious Education (PAK) in schools has an important role in shaping student character. PAK teachers are responsible for transferring Christian religious values into students' daily lives. aims to describe the responsibilities of PAK teachers in shaping students' character. The literature study used is by collecting data from relevant sources showing that PAK teachers have the responsibility to provide good examples, teach with dedication, and guide students in applying the teachings. Christianity in everyday life. The implication of this research is the need to increase the role of PAK teachers in shaping student character so that they can have a positive impact in forming a generation with noble morals. Next, you can focus on developing effective learning strategies in shaping student character through Christian religious education. Christian Religious Education Teachers have a very heavy responsibility in forming good and commendable student character. In the current unstoppable conditions, where development continues to occur without paying attention to ethics, morals and human character, the role of various parties, including Christian Religious Education teachers, is very necessary in controlling and developing effective and innovative student character. The conclusion of this journal confirms that Christian Religious Education teachers hold a great responsibility in forming students' character and moral values. With the right teaching approach, teachers can play an important role in forming good and responsible student character. Christian Religious Education (PAK) in schools has an important role in shaping student character. PAK teachers are responsible for transferring Christian religious values into students' daily lives. aims to describe the responsibilities of PAK teachers in shaping students' character. The literature study used is by collecting data from relevant sources showing that PAK teachers have the responsibility to provide good examples, teach with dedication, and guide students in applying the teachings. Christianity in everyday life. The implication of this research is the need to increase the role of PAK teachers in shaping student character so that they can have a positive impact in forming a generation with noble morals. Next, you can focus on developing effective learning strategies in shaping student character through Christian religious education. Christian Religious Education Teachers have a very heavy responsibility in forming good and commendable student character. In the current unstoppable conditions, where development continues to occur without paying attention to ethics, morals and human character, the role of various parties, including Christian Religious Education teachers, is very necessary in controlling and developing effective and innovative student character. The conclusion of this journal confirms that Christian Religious Education teachers hold a great responsibility in forming students' character and moral values. With the right teaching approach, teachers can play an important role in forming good and responsible student character. Christian Religious Education (PAK) in schools has an important role in shaping student character. PAK teachers are responsible for transferring Christian religious values into students' daily lives. aims to describe the responsibilities of PAK teachers in shaping students' character. The literature study used is by collecting data from relevant sources showing that PAK teachers have the responsibility to provide good examples, teach with dedication, and guide students in applying the teachings. Christianity in everyday life. The implication of this research is the need to increase the role of PAK teachers in shaping student character so that they can have a positive impact in forming a generation with noble morals. Next, you can focus on developing effective learning strategies in shaping student character through Christian religious education. Christian Religious Education Teachers have a very heavy responsibility in forming good and commendable student character. In the current unstoppable conditions, where development continues to occur without paying attention to ethics, morals and human character, the role of various parties, including Christian Religious Education teachers, is very necessary in controlling and developing effective and innovative student character.